Development of E-Aural Book Lawang Sewu Integrated with AKM Class to Improve Fourth-Grade Students’ Paragraph Comprehension - Amalia, Ashrifa Nur; Purwati, Panca Dewi (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aimed to develop and examine the effectiveness of the E-Aural Book Lawang Sewu integrated with AKM Class as a digital learning medium to improve elementary school students’ ability to analyze paragraph content in Indonesian language learning. The study employed a research and development (R&D) design consisting of needs analysis, media design, expert validation, small-scale trials, and large-scale implementation. The developed media integrates text, illustrations, audio narration, and AKM-based evaluation tasks to support students’ listening and analytical skills in identifying main and supporting sentences in aural texts. The validation results indicated that the developed media was highly feasible for instructional use, with validation scores of 96.125% from the material expert and 96.25% from the media expert. The effectiveness of the media was tested through pretest and posttest assessments during classroom implementation using the Think-Pair-Share (TPS) learning model. The results showed a significant improvement in students’ learning outcomes, as indicated by an increase in the average score from 59.40 in the pretest to 78.80 in the posttest. Statistical analysis using a paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between students’ performance before and after the implementation of the media. Furthermore, the N-Gain score of 0.48 indicated a moderate level of improvement. These findings suggest that the E-Aural Book Lawang Sewu integrated with AKM Class is effective in enhancing students’ comprehension and paragraph analysis skills in elementary Indonesian language learning.